We can do it: learning to try during the COVID19 Pandemic in Brazil - Oliveira, Augusto Vinicius de (Universidade Estadual Paulista (Unesp), 2020)
In this episode of the Foreign Language Learner Podcast, a student in the second year of Languages & Literature course at Unesp - São José do Rio Preto talks about living in the Covid19 pandemic.
Nível de proficiência de produção oral autoavaliado pelo aluno: B2
Keywords: COVID19 Pandemic; English as a foreign language; Pandemias; COVID-19; Língua inglesa Pronúncia estrangeira